The customary law nature of sustainable forest management states practice in Central America and European Union - Assembe-Mvondo, Samuel (2010)
Sustainable forest management (SFM) has become one of major environmental debates for the international community. This is because of the multifunctional importance of forest resources for the entire planet, namely ecological, socio-economic, cultural and climatic balance. General awareness of the multifunctional importance of forests unfortunately coincides with the observed increase of threats to these ‘international public goods’. To tackle continuous deforestation and degradation, the international community through the UNFF and its predecessors has attempted to adopt an international legally-binding agreement on sustainable management based on the Forest Principles. The narrow success of such international negotiations led to explore another option to this issue through the review of some regional agreements based on the inductive approach. This method is used by International Court of Justice for seeking the customary international law through the States behaviours or conducts. The paper is focussed on two regional regimes on SFM: the Central America Regional Convention and the European Union Resolution related sustainable forests management. The examination of States practice shows that such regional instruments fulfil all the requirements for having the status of the emerging customary law at these regions.